Designing Collaborative Systems A Practical Guide to Ethnography - Crabtree, Andy. (Computer Supported Cooperative Work, 2003)
Designing Collaborative Systems: A Practical Guide to Ethnography introduces a new 'ethnographic' approach that will enable designers to create collaborative and interactive systems, which are employed successfully in real-world settings. This new approach, adapted from the field of social research, considers both the social circumstances and the level and type of human interaction involved, thereby ensuring that future ethnographic systems are as user-friendly and as effective as possible. This book provides the practitioner with an invaluable introduction to this approach, and presents a unique set of practical strategies for incorporating it into the design process. Divided into four distinct sections with practical examples throughout, the book covers: - the requirements problem; - ethnographic practices for describing and analysing cooperative work; - the design process; and - the role of ethnography when evaluating systems supporting cooperative work. "Of the various perspectives that jostle together under the rubric of ethnography, ethnomethodology has often held the most appeal for designers. Yet, surprisingly, there has not been a systematic explication of ethnography and ethnomethodology for the purposes of system design. Andy Crabtree puts this to rights in a comprehensive, informative, and accessible practical guide which will be of great value to not only designers but also the ethnographers who work with them." (Graham Button, Lab. Director, Xerox Research Centre, Europe) "Not only is the book a must for those interested in bringing a social dimension to the system design process, it also makes a significant contribution to ethnomethodology." (Professor John A. Hughes, Lancaster University, UK).